2021
DOI: 10.5944/ried.24.2.29078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación Remota de Aprendizajes en la Universidad: decisiones docentes para encarar un nuevo desafío

Abstract: La pandemia por COVID-19 y la suspensión de actividades presenciales enfrentó a las universidades con el desafío de remotizar sus funciones. Este trabajo se propone caracterizar propuestas de evaluación de aprendizajes diseñadas, al inicio del confinamiento, por docentes de grado y posgrado de ciencias de la salud en el contexto de una propuesta de Formación para la Virtualización de la Enseñanza (FVE) de un Instituto Universitario. Este estudio descriptivo-interpretativo analiza, desde un enfoque cualitativo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
3
0
11
Order By: Relevance
“…Perhaps the next step would be to discover, in agreement with References [11,30], if the perception of impact detected improved or not the quality of teaching. However, the application of this new knowledge was not without its difficulties, as the study demonstrated that the professors had problems in the application of knowledge related with the evaluation of learning in online teaching, as also pointed out by authors, such as References [39,40]. Transferring the parameters of an in-person evaluation to online evaluation is impossible, considering that in most occasions, the evaluation models developed for in-person teaching are based on collecting information on the contents that students are able to recall, as a result of a transmission-based methodology.…”
Section: Discussionmentioning
confidence: 80%
“…Perhaps the next step would be to discover, in agreement with References [11,30], if the perception of impact detected improved or not the quality of teaching. However, the application of this new knowledge was not without its difficulties, as the study demonstrated that the professors had problems in the application of knowledge related with the evaluation of learning in online teaching, as also pointed out by authors, such as References [39,40]. Transferring the parameters of an in-person evaluation to online evaluation is impossible, considering that in most occasions, the evaluation models developed for in-person teaching are based on collecting information on the contents that students are able to recall, as a result of a transmission-based methodology.…”
Section: Discussionmentioning
confidence: 80%
“…Han sido muchos los desafíos que ha tenido que enfrentar la educación desde el momento que se volvió a distancia por el confinamiento generado a nivel mundial. Es así que se tuvieron que implementar nuevas metodologías de enseñanza para dar continuidad a los procesos educativos (Schwartzman et al, 2021). Metodologías como el aula invertida, el aprendizaje basado en proyectos y el aprendizaje colaborativo mediados por las TIC, han facilitado los aprendizajes y dado otra perspectiva al proceso de enseñanza aprendizaje (Fernández-Esteban et al, 2021).…”
Section: Desafíos De Las Tic En La Educaciónunclassified
“…There have been many challenges that education has had to face since it was transformed into a distance education due to the confinement that was had worldwide by the pandemic, which generated that new teaching methodologies had to be implemented to continuity of education, (Schwartzman et al, 2021). Teaching mediated by technologies has allowed a greater emphasis on implementing methodologies such as flipped classroom, project-based learning, collaborative learning, which facilitated learning, giving another perspective to the teaching-learning process of hybrid education (Fernández-Esteban et al, 2021).…”
Section: Challenges Of Information and Communication Technologies In Educationmentioning
confidence: 99%
“…Analizar la información en la investigación es hacer uso del método sistematización de experiencias (Carvajal, 2018;Jara, 2020), el mismo que permite interpretar de forma crítica una o varias vivencias ordenando y reconstruyendo las mismas para explicar el proceso con sentido lógico, algunos factores intervinientes, las relaciones acontecidas y el sustento que justifica determinada práctica. Además, se contrastan con otras experiencias y la teoría existente, significando una contribución desde y para la práctica (Unday & Valero, 2017;Schwartzman et al, 2021). En la Figura 1 se esboza el diseño de la metodología empleada, resaltando el uso de bases científicas suficientes (Teoría necesaria), para las comparaciones entre experiencias de otras realidades y a la luz de la teoría.…”
Section: Métodounclassified